Peluang dan Tantangan Belajar Bahasa Indonesia Sebagai Bahasa Asing: Studi Kasus Pelajar Thailand - Feny Arta Melinda; Mutia Febriyana; Isthifa Kemal (Tarbiatuna: Journal of Islamic Education Studies, 2024)
Year by year Indonesia's economic growth is increasingly advanced. This is marked by the development of industry and the large number of business people coming to Indonesia. Along with this, Indonesian as a communication tool began to develop and was widely used by foreign speakers. Thus, Indonesian also has the potential to become an international language. The focus of this research is the opportunities and challenges that occur when Thai students study a foreign language, namely Indonesian. The data source in this research is at the PattanakanSuksa Minithi School within the framework of the international community service program. The development of the Indonesian language is mostly carried out by the government and universities. It is hoped that the government will take steps to globalize the Indonesian language by making several efforts to spread the language for foreign students to learn Indonesian. This research touches on aspects such as teaching grammar, vocabulary, and communication skills in everyday situations. Additionally, information about cultural approaches, assessments, and support resources provided to program participants may be included.